Similar words, different meanings: a natural semantic metalanguage exploration of cultural differences - Hazidi Bin Haji Abdul Hamid (Penerbit UKM, 2002)
Anna Wierbicka and other writers of Natural Semantic Metalanguage (henceforth NSM) often argue that anthropologists and psychologists, particularly Western ones, are wrong for applying concepts like mind, anger and depression to foreign cultures because these cultures do not have words with similar intention and extensions. Their critics on the other hand argue that the NSM critique is unjustified because while other cultures do not necessarily have similar words, they must have corresponding concepts simply because people in these other cultures, like in Malaysia, experience feelings like these (M, Immler 1991:51). This paper intends to show that the NSM critique is justified because these corresponding concepts can be similar to a certain extent but can also carry great semantic difference when broken down to their more basic elements of meaning. More importantly, this will be done using analysis of the Malay language.